THE QUALITY OF HEALTH SERVICES WITH INPATIENT SATISFACTION IN RS GRAHA JUANDA - Fitriyastanti, Devi; Jumaedi, Jumaedi; Azzahra, Rusliana (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Public demand for health services is increasing every year, so it is important to maintain the quality of services provided. Five main factors influence the quality of health services, namely tangible, reliability, responsiveness, assurance, and empathy. The change in vision at Graha Juanda Hospital in the short term impacts the quality of health services. This study aimed to determine the description of the quality of health services with inpatient satisfaction. Methods: This research uses a descriptive study with a quantitative approach. The study population was all inpatients at Graha Juanda Hospital in April 2024. The research sample consisted of 68 respondents using the sampling technique of Voluntary Response. Results: based on 5 research variables in the quality of health services, it shows the variables that have a poor category consist of tangible, reliability and responsiveness. Meanwhile, only assurance has a good category. Conclusion: The quality of health services at Graha Juanda Hospital from 5 dimensions of quality is mostly dominated by poor quality of health services.